Ways of Development of Stock Market in the Economy of Country - Nematovich, Хamzayev Azizbek (European Journal of Life Safety and Stability (2660-9630), 2022)
This article discusses the issues of establishing the necessary organizational structure for determining and controlling the achievement of strategic goals in the activities of Joint-stock companies, as well as ensuring the possibility of making decisions related to the development of the stock market, the totality of relations between the management system of Joint-stock companies and other interested parties, including the management of Joint-stock companies.